BET inhibitors synergize with sunitinib in melanoma through GDF15 suppression - Zeng, Furong; Li, Yayun; Meng, Yu; Sun, Huiyan; He, Yi; Yin, Mingzhu; Chen, Xiang; Deng, Guangtong (Experimental & molecular medicine, 2023)
Targeting bromodomain and extra-terminal domain (BET) proteins has shown a promising therapeutic effect on melanoma. The development of strategies to better kill melanoma cells with BET inhibitor treatment may provide new clinical applications. Here, we used a drug synergy screening approach to combine JQ1 with 240 antitumor drugs from the Food and Drug Administration (FDA)-approved drug library and found that sunitinib synergizes with BET inhibitors in melanoma cells. We further demonstrated that BET inhibitors synergize with sunitinib in melanoma by inducing apoptosis and cell cycle arrest. Mechanistically, BET inhibitors sensitize melanoma cells to sunitinib by inhibiting GDF15 expression. Strikingly, GDF15 is transcriptionally regulated directly by BRD4 or indirectly by the BRD4/IL6/STAT3 axis. Xenograft assays revealed that the combination of BET inhibitors with sunitinib causes melanoma suppression in vivo. Altogether, these findings suggest that BET inhibitor-mediated GDF15 inhibition plays a critical role in enhancing sunitinib sensitivity in melanoma, indicating that BET inhibitors synergize with sunitinib in melanoma. Cancer: a drug combination for combating melanoma Drugs that target proteins involved in issuing stop and start commands to cancer-related genes help to sensitize melanoma cells to a widely used anti-cancer therapy, leading to tumor shrinkage in mice. Furong Zeng from Central South University in Changsha, China, and colleagues screened 240 approved anti-cancer agents in search of molecules that work synergistically with a BET inhibitor, an inhibitor of these proteins, to induce the death of melanoma cells. They found that a protein targeted by BET inhibitors (JQ1 and NHWD-870) regulates a growth factor protein, whose altered expression then helps to sensitize melanoma cells to sunitinib. Sunitinib is approved to treat several types of cancer and works by targeting many different kinds of kinase enzymes. The combination of BET inhibitors and sunitinib showed synergistic antitumor effects in a mouse model of melanoma.